2019
DOI: 10.3324/haematol.2018.205385
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic niche drives FLT3-ITD acute myeloid leukemia resistance to quizartinib via STAT5-and hypoxia-dependent upregulation of AXL

Abstract: Internal tandem duplication in Fms-like tyrosine kinase 3 (FLT3-ITD) is the most frequent mutation observed in acute myeloid leukemia (AML) and correlates with poor prognosis. FLT3 tyrosine kinase inhibitors are promising for targeted therapy. Here, we investigated mechanisms dampening the response to the FLT3 inhibitor quizartinib, which is specific to the hematopoietic niche. Using AML primary samples and cell lines, we demonstrate that convergent signals from the hematopoietic microenvironment drive FLT3-IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 51 publications
2
70
0
Order By: Relevance
“…7 However, TAM receptors were also reported to impede cancer cells through stimulation of tumor cell-targeting immune cells. 8 The new findings reported by Dumas et al 2 confirm an important cancer-protective role for the stromal microenvironment, mechanistically identifying that it induces cytokine production and hypoxic conditions to trigger the activation of AXL and the transcription factor STAT5 in FLT3-ITD + AML ( Figure 1A). The authors further show that stroma-induced expression of AXL, mediated by STAT5, drives progression of the disease.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…7 However, TAM receptors were also reported to impede cancer cells through stimulation of tumor cell-targeting immune cells. 8 The new findings reported by Dumas et al 2 confirm an important cancer-protective role for the stromal microenvironment, mechanistically identifying that it induces cytokine production and hypoxic conditions to trigger the activation of AXL and the transcription factor STAT5 in FLT3-ITD + AML ( Figure 1A). The authors further show that stroma-induced expression of AXL, mediated by STAT5, drives progression of the disease.…”
mentioning
confidence: 65%
“…The new study by Dumas et al in this issue of the Journal unravels mechanisms involving the tyrosine kinase receptor AXL contributing to the development of resistance to quizartinib in FLT3-ITD + AML. 2 AXL belongs to the family of TAM receptors, and together with two other members, TYRO3 and MER, it was first shown to have malignant roles in solid cancers. 3,4 AXL was identified as one of the most prominently activated tyrosine kinase receptors in colorectal, esophageal, thyroid, breast, prostate and lung carcinomas, and its activation was associated with transforming growth factor beta (TGFβ) signaling.…”
mentioning
confidence: 99%
“…Apart from AXL's role in promoting tumorintrinsic resistance, a recent study has shown that marrow stromal cells support increased phosphorylation of STAT5, which in turn leads to increased AXL activity that drives quizartinib resistance both in vitro and in vivo. 45 The study showed that the hypoxic marrow microenvironment further contributed to increased AXL activity, and thereby, aids quizartinib resistance in an extrinsic manner. 45…”
Section: Intrinsic Resistance Mechanismsmentioning
confidence: 97%
“…45 The study showed that the hypoxic marrow microenvironment further contributed to increased AXL activity, and thereby, aids quizartinib resistance in an extrinsic manner. 45…”
Section: Intrinsic Resistance Mechanismsmentioning
confidence: 97%
“…Each TKI has its own unique adverse effect profile, and in the era of combining numerous novel therapies, factors such as optimal dosing, schedule and sequence need to be determined to prevent toxicity. Furthermore, with continued use, these TKIs are prone to resistance through various mechanisms, particularly with acquisition of TKD mutations that make both sofarenib and quizartinib ineffective (Park et al, ; Alvarado et al, ; Smith et al, ; Dumas et al, ). HSCT should be considered in CR1 in fit patients with FLT3 ‐ITD‐mutation, but the advantage is unknown in patients with FLT3 ‐TKD.…”
Section: Targeted Therapies In Amlmentioning
confidence: 99%